2006
DOI: 10.1038/sj.npp.1301036
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effects of the Corticotropin-Releasing Factor 1 Receptor Antagonist, SSR125543, and the Vasopressin 1b Receptor Antagonist, SSR149415, in a DRL-72 s Schedule in the Rat

Abstract: The vasopressin 1b receptor antagonist, SSR149415, and the corticotropin-releasing factor 1 receptor antagonist, SSR125543, are orally active non-peptidic compounds with anxiolytic-and antidepressant-like activities in animal models. Presently, SSR149415 and SSR125543 were evaluated in a differential reinforcement of low-rate 72 s (DRL-72 s) schedule, a procedure known to respond differentially to antidepressants and anxiolytics. Male Wistar rats were trained to lever-press for food reinforcement, but only lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Burst responses are reported to be increased by the nondelivery of an expected reward and have been associated with frustration, impulsivity, and other emotional reactions. In addition, burst responding has been shown to be sensitive to benzodiazepine-like compounds (Richards and Seiden 1991;Richards et al 1993Richards et al , 1994, whereas responses with longer duration IRTs have been shown to be sensitive to antidepressant drugs (Cohen et al 1997;Louis et al 2006). Consequently, one can consider burst responding as an expression of frustration to the "penalty" of reinforcement omission and clock reset.…”
Section: Discussionmentioning
confidence: 99%
“…Burst responses are reported to be increased by the nondelivery of an expected reward and have been associated with frustration, impulsivity, and other emotional reactions. In addition, burst responding has been shown to be sensitive to benzodiazepine-like compounds (Richards and Seiden 1991;Richards et al 1993Richards et al , 1994, whereas responses with longer duration IRTs have been shown to be sensitive to antidepressant drugs (Cohen et al 1997;Louis et al 2006). Consequently, one can consider burst responding as an expression of frustration to the "penalty" of reinforcement omission and clock reset.…”
Section: Discussionmentioning
confidence: 99%
“…forced swim test, chronic mild stress) as well as other models (e.g. olfactory bulbectomy, Flinder's sensitive line) that are used to determine the efficacy of potential anti-depressant and anxiolytic drugs (Griebel et al 2002; Overstreet and Griebel 2005; Stemmelin et al 2005; Louis et al 2006; Salomé et al 2006; Shimazaki et al 2006; Hodgson et al 2007; Iijima and Chaki 2007). Peripheral and central pretreatment with SSR149415 reduces anxiety and depressive-related behaviour in these tests with high compatibility between the findings of these studies.…”
Section: V1b Receptor Ko Micementioning
confidence: 99%
“…These negative emotional states following frustration may have an important impact on subsequent consumption in drug addicts or patients suffering from food eating disorders. In rodents, frustration models have been mainly implemented to induce a depressive-like state in rats exposed to the total or partial omission of an expected reward (Gray et al 1977;Louis et al 2006). Animal models of frustrated food or drug consumption can be of particular relevance to study the behavioural and neurobiological consequences related to the emotional states generated by these frustrated conditions that often occur in drug addicts and food eating disorder patients.…”
Section: Introductionmentioning
confidence: 99%